2012
DOI: 10.1089/tmj.2011.0119
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Management via Mobile Phones: A Systematic Review

Abstract: The studies evaluated showed promise in using mobile phones to help people with diabetes manage their condition effectively. However, many of these studies lacked sufficient sample sizes or intervention lengths to determine whether the results might be clinically or statistically significant. Future research should examine other key issues, such as provider perceptions, integration into a healthcare practice, and cost, which would provide important insight into the use of mobile phones for chronic disease mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
238
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(256 citation statements)
references
References 29 publications
12
238
2
Order By: Relevance
“…These interventions were primarily designed to improve patients' self-management behaviours, such as adherence to treatment and monitoring of their condition [50,51]. The findings of the present review support previous literature that has found mobile technology to be an acceptable platform to deliver interventions to patients with chronic conditions, regardless of the patients' type of disease, age, gender and experience with technology [52][53][54][55][56]. Generally, the majority of patients included in studies of the present review found mobile interventions easy to use and engaging, regardless of the type of device used (e.g.…”
Section: Findings In the Context Of Other Literaturesupporting
confidence: 79%
“…These interventions were primarily designed to improve patients' self-management behaviours, such as adherence to treatment and monitoring of their condition [50,51]. The findings of the present review support previous literature that has found mobile technology to be an acceptable platform to deliver interventions to patients with chronic conditions, regardless of the patients' type of disease, age, gender and experience with technology [52][53][54][55][56]. Generally, the majority of patients included in studies of the present review found mobile interventions easy to use and engaging, regardless of the type of device used (e.g.…”
Section: Findings In the Context Of Other Literaturesupporting
confidence: 79%
“…8 Studies of mobile phone-based interventions have had varied success in improving self -management and glycemic control in individuals with diabetes. 9,10 One explanation is that mobile phones are a platform, not a solution in itself, and interventions vary widely. A major gap in the literature is the lack of behavioral models to explain how these interventions improve diabetes self-management.…”
Section: Discussionmentioning
confidence: 99%
“…22 Blood glucose recording and activity logs were the most common features of commercially available mobile apps for diabetes. 23 Majority (71%) of the mobile phone-based interventions for T2D 24 used study-specific apps with more features than simple SMS. These features (diary/log, reminders, and information/education) varied according to study requirement and many studies had multiple functions.…”
Section: Type 2 Diabetesmentioning
confidence: 99%